Implementasi Sistem Pengelolaan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) sebagai Upaya Peningkatan Kepatuhan Wajib Pajak pada Badan Pendapatan Daerah Kota Medan - Mutia Syahara; Henny Andriani Wirananda; Alya Sahputri Siregar; Cut Tasya Marshanda (CV. BAROKAH PUBLISHER, 2026)
Rural and Urban Land and Building Tax (PBB-P2) is one of the important sources for increasing Regional Original Income (PAD). However, in practice, the level of public compliance with tax obligations remains a challenge in various regions, including the City of Medan. This community service activity aims to educate and assist the public regarding the PBB-P2 management system implemented by the Medan City Revenue Agency. The methods of the activities were carried out thru field observations, interviews with tax administrators, tax socialization, and assistance to taxpayers in understanding the payment procedures and updating tax object data. The results of the activities show that the use of a digital-based service system and tax education activities can enhance the public's understanding of tax obligations. In addition, direct socialization helps the community understand the tax payment procedures and the importance of regularly updating tax object data. However, there are several obstacles, such as the low tax literacy of the community and limited access to technology for some taxpayers. Therefore, continuous socialization and improvement in the quality of tax services are needed so that public compliance in paying taxes can continue to increase.